Correlation Between Dust Exposure, Individual Characteristic to Lung Functionin Merchants Around Gresik Industrial Area - Rachmania Helmy (Universitas Airlangga, 2019)
Dust is one of the air pollutants that have high toxicity level. Merchants society are risk groups exposed to respiratory system disorders, especially lung physiology problem. This study aims to analyze the correlation between dust exposure and individual characteristic with lung function on permanent merchants around Gresik industrial area. This research was a quantitative observational research with cross sectional design. Sample on The research are 13 merchants at exposed area as study group and 11 merchants at non exposed area as control group. Independent variables studied are individual characteristics and exposure to dust, while the dependent variable is the lungs physiological status. Data were collected by questionnaires for individual characteristics and spirometer to assess lung physiological status. The result showed that air quality such as dust was exceeded from environmental quality standards at study group area. Based on chi square statistical test, individual characteristics correlated to the lung physiological status of the study group traders were age and duration of exposure. There was a correlation of dust exposure to the lung physiological status of merchants around the industrial area of Manyar District, Gresik. Thereis a difference in lung physiology status between the two groups with a p value of 0.000. The conclusion of this study is there was a correlation between dust exposure,age, and duration of exposure to the lung physiological status of merchants around the industrial area of Manyar District, Gresik.